Partial mechanical stimulation facilitates the growth of the rhizomatous plant Leymus secalinus: modulation by clonal integration - Sui, Yuan (Oxford University Press, 2011)
BACKGROUND AND AIMS: Mechanical stimulation (MS) often induces plants to undergo thigmomorphogenesis and to synthesize an array of signalling substances. In clonal plants, connected ramets often share resources and hormones. However, little is known about whether and how clonal integration influences the ability of clonal plants to withstand MS. We hypothesized that the effects of MS may be modulated by clonal integration. METHODS: We conducted an experiment in which ramet pairs of Leymus secalinus were subjected to three treatments: (1) connected ramet pairs under a homogeneous condition [i.e. the proximal (relatively old) and distal (relatively young) ramets were not mechanically stressed]; (2) connected ramet pairs under a heterogeneous condition (i.e. the proximal ramet was mechanically stressed but the distal ramet was not); and (3) disconnected ramet pairs under the same condition as in treatment 2. At the end of the experiment, we harvested all plants and determined their biomass and allocation. KEY RESULTS: Clonal integration had no significant influence on measured traits of distal L. secalinus ramets without MS. However, under MS, plants with distal ramets that were connected to a mother ramet produced more total plant biomass, below-ground biomass, ramets and total rhizome length than those that were not connected. Partial MS exerted local effects on stimulated ramets and remote effects on connected unstimulated ramets. Partial MS increased total biomass, root/shoot ratio, number of ramets and total rhizome length of stimulated proximal ramets, and increased total biomass, root weight ratio, number of ramets and total rhizome length of connected unstimulated ramets due to clonal integration. CONCLUSIONS: These findings suggest that thigmomorphogenesis may protect plants from the stresses caused by high winds or trampling and that thigmomorphogenesis can be strongly modulated by the degree of clonal integration.